Role of security guards in Code Black events in medical and surgical settings: A retrospective chart audit. (28th May 2020) - Muir‐Cochrane, Eimear; Muller, Amanda; Fu, Yanfen; Oster, Candice
Abstract: The prevalence of security guards in health care settings is growing worldwide. There is a need to explore and understand their role and actions to inform policy and training and support least restrictive practices in health care. The aim of this study was to conduct a retrospective chart audit of security guard logs to investigate security guard involvement in Code Blacks, called in emergency situations of personal threats including patient and/or visitor violence, in medical and surgical wards in a large metropolitan health network in South Australia. Security guards attended 1664 Code Blacks (0.63% of admissions) over the 2.5‐year study period. Events were more frequently reported in medical than surgical wards. The most common reasons for security guard attendance were patients threatening/harming staff and patients threatening/harming themselves. The most frequent security guard actions were "Attend only/standby, " "Physical restraint, " and "Patient located and returned to the ward." The most frequent outcomes were physical restraint, chemical restraint, and de‐escalation respectively. Results highlight the imperative that health services maintain and increase efforts to support least restrictive practice through policy directives and staff training.